HCV and HIV infection and co-infection: injecting drug use and sexual behavior, AjUDE-Brasil I Project - Keli Bahia Felicíssimo Zocratto; Waleska Teixeira Caiaffa; Fernando Augusto Proietti; Anna Bárbara Carneiro-Proietti; Sueli Aparecida Mingoti; Geraldo José Coelho Ribeiro
This study aimed to characterize sexual and drug-use behaviors in injecting drug users (IDUs) in relation to single hepatitis C virus (HCV) and human immunodeficiency virus (HIV) infection and HCV/HIV co-infection. The sample consisted of 272 IDUs enrolled in the AjUDE-Brasil I Project, a cross-sectional multi-center study conducted in five Brazilian cities in 1998. Data were collected with a structured questionnaire using self-reported risk behavior, and HCV and HIV serological status used ELISA on filter paper. IDUs were clustered in four distinct groups: HCV/HIV seronegative; HCV mono-infected; HIV mono-infected; and HCV/HIV co-infected. Active sharing of injecting equipment was associated with HCV infection (p = 0.001). Sexual behavior variables, especially male same-sex sexual relations, were consistently associated with HIV infection. HCV/HIV co-infection was associated with both sexual and drug use variables. It was possible to distinguish different behavioral indicators for HCV and HIV infection and co-infection in this population.